PERBANDINGAN TINGKAT PRODUKSI LADA HITAM DAN LADA PUTIH DI DESA SUMBER HARAPAN KECAMATAN SAMBAS - Andrayani, Ketti; Nurfariza, Nurfariza (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
Pepper (Piper ningrum L.) is a strategic spice crop in global trade. Two types of pepper are commonly traded in both domestic and international markets: white pepper and black pepper. Sambas Regency is one of the pepper centers in West Kalimantan Province. Sumber Harapan Village is one of the pepper-producing villages in Sambas Regency. Some residents of Sumber Harapan Village have pepper, but the pepper production is not as abundant as in other areas. The pepper produced by the Sumber Harapan Village community is divided into two types: black pepper and white pepper. This study used a quantitative research method, using a total sampling method with 16 respondents. This study aimed to compare the production levels of black pepper and white pepper in Sumber Harapan Village. The results of this study indicate that the ratio of black pepper to white pepper production in Sumber Harapan Village in 2023 was 1:9, meaning that for every 1 kg of black pepper, there are approximately 9 kg of white pepper. The ratio of black pepper to white pepper production in Sumber Harapan Village in 2024 was 1:7, meaning that if a farmer produces 1 kg of black pepper, they will also produce 7 kg of white pepper. Keywords: Black Pepper and White Pepper, Comparison, Production Level.